PERAN MAMMALIAN TARGET OF RAPAMYCIN DALAM EPILEPSI - Machlusil Husna,* Shahdevi Nandar Kurniawan* (Neurona Majalah Kedokteran Neuro Sains, 2017)
TARGET OF RAPAMYCIN MTOR IS A LARGE SERINETHREONINE KINASE WHICH PLAYS MAJOR ROLE IN MANY CELLULAR PROCESSES SUCH AS GROWTH REGULATION AND CELLULAR METABOLISM DEVELOPMENT AND PROLIFERATION OF ADAPTIVE IMMUNE FUNCTION AND CELL DEATH THROUGH APOPTOSIS AND AUTOPHAGY THE MTOR SIGNAL PATHWAY WORKS AS MOLECULAR SYSTEM INTEGRATOR TO SUPPORT CELLULAR AND ORGANISM INTERACTIONS WITH THE ENVIRONMENT